PREVALENCE OF GIARDIA LAMBLIA IN DIARRHEA IN SOME HEALTH CENTERS IN DUHOK CITY, IRAQ - KHALID, KAVEEN SALIM; AL-BADRANI, MOHAMMED ADNAN; ISSA, ARAZ RAMADHAN (Journal of Duhok University, 2023)
Giardia lamblia is an intestinal protozoan disease that is common in developing nations, particularly among children, as a result of inadequate sanitation, poor sewage drainage, and a lack of attention to personal health. The purpose of this study was to estimate the incidence and identify the risk factors for Giardia lamblia infection in children who had been attended in different health centers in Duhok city, North of Iraq. A total of 642 fecal samples were collected from children aged from (0 - 6) years in different health centers in Duhok city during the period between June 2022 to November 2022, and were examined for detection of Giardia lamblia by using direct microscopic examination and floatation method. Out of 642 samples examined, 61 (9.50%) were positive for Giardia lamblia. The age group (5-6) years had the highest rate of infection (16.74%). The prevalence rate among males (10.09%) was higher than females (8.88%). According to months the greatest rates of infection being observed in June and July (2.80 and 2.65%, respectively), and lowest rate was observed in November (0.16%). Based on the results of this study, it is concluded that the prevalence of Giardia lamblia parasite in Duhok cities is still high and it’s required effective techniques and plans to stop the spread of these parasites